A critical heat flux model for unilateral heating rectangular narrow channel. (July 2020) - Song, Gongle; Liang, Yu; Sun, Rulei; Zhang, Dalin; Deng, Jian; Su, G.H.; Tian, Wenxi; Qiu, Suizheng
Highlights: A three-fluid transient model is developed for rectangular narrow channels. The model contains a complete set of field equations and constitutive equations. The finite difference method is used to solve the three-fluid transient model. The average error of the model is 6.8%, and the standard deviation is 0.24. Abstract: In most designs, the coolant channel is under non-uniform heating, mainly one-sided heating. There is no clear understanding of the problem of unilateral heating. In order to deepen the understanding of the mechanism of CHF in the unilateral heating rectangular narrow channel, a three-fluid transient model of annular flow was developed for the rectangular narrow channel heated on one side. Basic conservation equations were established for the liquid film, droplets, and vapor core respectively, and the constitutive model involved void fraction, interphase friction, wall friction, and the calculation of entrainment rate and deposition rate. The finite difference method was used to solve the three-fluid transient model of annular flow numerically. Within a wide range of experimental parameters (pressure 0.1–15.0 MPa, mass flux 300.0–17100.0 kg/m 2 s, inlet subcooling 6.5–292.5 K, length of channel section 4.0–50.0 mm, width of channel section 2.0–6.35 mm, length of channel 200–1550 mm, and CHF value 0.63–28.4 MW/m 2 ), most of the calculation error of the model were within 30%, which proved the validity of the three-fluid transient model of annular flow.